Motivation for myopia prevention: a preliminary test of the trans-contextual model - Chan, D.; Hagger, Martin; Fung, Y.; Fung, Y. (Routledge, 2012)
Background: Near-work is one of the major antecedents of myopia. Therefore, this study aims to apply the trans-contextual model to understand how self-determined (SD) motivation of myopia prevention and autonomy support are associated with the SD-motivation and behaviour of reading at an optimal distance. Methods: Participants (108 undergraduate students) completed questionnaires of the study variables one month before we assessed their 18 EHPS 2012 abstracts Downloaded by [Chinese University of Hong Kong] at 01:22 17 June 2014 voluntary reading distance (by an ultrasound-device) at a laboratory setting. We analysed the data by partial-least-square modeling. Findings: Consistent with the hypothesis, SD-motivation of myopia prevention was predicted positively by autonomy support from significant others (i.e., parents and optometrists), and it was the significant predictor of the SD-motivation of optimal-distance-reading. Participants who had higher levels of SD-motivation of optimal-distance-reading tended to read further away from the reading material. Discussion: The trans-contextual model may be a useful framework to explain the top-down motivational process of myopia prevention.